The Effect of Core Stability Exercise on Decreasing Angle of Trunk Rotation Degree in Idiophatic Scoliosis in Junior High School Student - Windy Lathifa; Sukadarwanto Sukadarwanto; Afif Ghufroni (Medica Hospitalia : Journal of Clinical Medicine, 2024)
Background : Scoliosis is a group of conditions consisting of changes in the shape and position of the spine on the lateral side that may be accompanied by rotation caused by various etiologies. Core stability exercise is a form of exercise that can be used to reduce the degree of scoliosis curve Objective : This study aims to determine the effect of core stability exercise on junior high school student (JHS). Methods : This study used a one group pre and post test with control design involving 32 students of SMP 2 Wonosari Klaten who were divided into 2 groups, using the blind randomized control trial method.  into 2 groups, namely a treatment group and a control group with a treatment group of 16 subjects  as intervention group given treatment of core stability exercise and a control group of 16 subjects  as control group without any treatment. The intervention was carried out for 5 weeks with a frequency of 3 times a week. Measuring the degree of the scoliosis curve using a scoliometer. The pre-test trunk rotation angle (ATR) value for the treatment group was found to be an average of 5.06º and a post-test ATR value of 4.75º. Meanwhile, in the control group, there was no change in the ATR value during the pre-test or post-test, which was 5.43º. Result : Statistical test of differences in pre-post test of treatment groups using the Wilcoxon test obtained a value of p = 0.025 (p < 0.05). Conculsion : From this study it was concluded that There is an effect of core stability exercise on reducing the scoliosis curve in junior high school student.